2019
DOI: 10.1159/000499580
|View full text |Cite
|
Sign up to set email alerts
|

Can Fetal Growth Velocity and First Trimester Maternal Biomarkers Improve the Prediction of Small-for-Gestational Age and Adverse Neonatal Outcome?

Abstract: <b><i>Background and Objectives:</i></b> The aim of this study was to evaluate the value of adding fetal growth velocity and first trimester maternal biomarkers to baseline screening, for the prediction of small-for-gestational age (SGA) and adverse neonatal outcomes. <b><i>Method:</i></b> A retrospective cohort study was conducted of singleton pregnancies in the Maastricht University Medical Centre between 2012 and 2016. The biomarkers PAPP-A, β-hCG, PlGF, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
1
14
1
Order By: Relevance
“…As far as we are concerned, there are few studies evaluating fetal weight and the well-being of the fetus with first-trimester NT measurements. [5] The number of patients was lower in previous studies when compared to the present study. We believe that the study contributes to the literature because the number of patients was significantly higher, and it is one of the few studies in the literature.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…As far as we are concerned, there are few studies evaluating fetal weight and the well-being of the fetus with first-trimester NT measurements. [5] The number of patients was lower in previous studies when compared to the present study. We believe that the study contributes to the literature because the number of patients was significantly higher, and it is one of the few studies in the literature.…”
Section: Discussioncontrasting
confidence: 78%
“…NT is defined as the subcutaneous fluid located under the skin at the back of the fetal neck measured between 11 weeks and 13 weeks + 6 days of gestation, regardless of whether it covers only the head or whole body, or presents septations. [5] The main mechanisms suggested for increased NT are a change in the composition of the extracellular matrix, heart, great artery anomalies, and impaired or delayed lymphatic development. [3] Fetuses with increased NT are at high risk for chromosomal, structural, and genetic anomalies, and generally, it is accepted as a non-specific sign of fetal abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…All HSROC curves are shown in Figure 2. Data for predicting admission to the NICU were available in 11 studies 12,[28][29][30][31][32][33][34][35][36][37] . Detection rates at 25% and 50% false-positive rates (FPRs) were 48% and 76%, respectively.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…According to the QUADAS-2 scale, four articles 12,28,29,34 had high risk of bias in the patient selection domain owing to the nested case-control design of the study. One study 31 raised some concerns in terms of patient selection because of its inappropriate exclusion of participants with EFW > 90 th percentile. However, this did not necessarily increase the risk of bias in the selection of our study population.…”
Section: Risk Of Bias Of Studiesmentioning
confidence: 99%
“…The importance of combination of serial ultrasonographic scans, fetal doppler parameters and biochemical parameters are well documented. In a retrospective study, Hendrix et al reported that it can be better for predict of SGA combination of first trimester PAPP-A, B-hCG, PIGF, and sFlt-1 and ultrasonographic growth velocity screening between 18-22 th and 30-34 th gestational weeks than baseline screening parameters alone 23 . In another retrospective study which included 23894 singleton pregnancies scanned between 19 and 24 weeks, Familiari et al showed that combination of mid-trimester fetal biometry, uterine artery doppler indices and maternal demographics characteristics can identify the majority of pregnancies at high risk for SGA birth and showed a higher performance for earlier gestational ages at birth and lower birth-weight centiles 24 .…”
Section: Discussionmentioning
confidence: 99%